First multi-redshift limits on post-epoch of reionization 21cm signal from z = 1.96-3.58 Using uGMRT - Chakraborty A.; Datta A.; Roy N.; Bharadwaj S.; Choudhury T.R.; Datta K.K.; Pal S.; Choudhury M.; Choudhuri S.; Dutta P.; Sarkar D. (My University, 2025)
Measurement of fluctuations in diffuse HI 21 cm background radiation from the post-reionization epoch (z ≤ 6) is a promising avenue to probe the large-scale structure of the universe and understand the evolution of galaxies. We observe the European Large Area ISO Survey-North 1 (ELAIS-N1) field at 300-500 MHz using the upgraded Giant Meterwave Radio Telescope (uGMRT) and employ the "foreground avoidance"technique to estimate the HI 21 cm power spectrum in the redshift range z = 1.96-3.58. Given the possible systematics that may remain in the data, we find the most stringent upper limits on the spherically averaged 21 cm power spectra at k ∼ 1.0 Mpc-1 are (58.87 mK)2, (61.49 mK)2, (60.89 mK)2, and (105.85 mK)2 at z = 1.96, 2.19, 2.62, and 3.58, respectively. We use this to constrain the product of neutral HI mass density (ΩHI) and HI bias (bHI) to the underlying dark matter density field, [ΩHIbHI], as 0.09, 0.11, 0.12, and 0.24 at z = 1.96, 2.19, 2.62, and 3.58, respectively. To the best of our knowledge these are the first limits on the HI 21 cm power spectra at the redshift range z = 1.96-3.58 and would play a significant role to constrain the models of galaxy formation and evolution. © 2021. The American Astronomical Society.